NAT2 gene polymorphism and development of multiple drug resistant tuberculosis in patients with HIV infection - N. V. Maltseva; I. B. Viktorova; O. M. Kazantseva; A. L. Khanin (Туберкулез и болезни лёгких, 2021)
The objective: to run the comparative study of frequencies of variants of polymorphic loci of NAT2 gene in the development of multiple drug resistant tuberculosis (MDR TB) and drug sensitive tuberculosis (DS TB) in patients with HIV infection.Subjects and Methods. 70 patients with TB/HIV co-infection at the age from 24 to 58 years old were examined when admitted to hospital.54 (77.1%) patients were new cases, the remaining 16 cases underwent repeated treatment. MDR TB was diagnosed in 47 patients: 33 patients had primary MDR, and 14 patients suﬀered from acquired MDR. Drug susceptible tuberculosis was diagnosed in 23 patients. Allele-speciﬁc PCR was used for genotyping of patients by rs1208, rs1799930, and rs1799929 polymorphic loci of N-acetyltransferase-2 (NAT2) gene.Results. A high probability of carriage of wild genotype of NAT2Arg197Arg(G590G) and allele NAT2Arg197(590G) was revealed in MDR TB(n = 70, OR = 3.63, p = 0.02 and OR = 2.24, p = 0.05, respectively) and it was found low in DS TB (n = 70, OR = 0.28, p = 0.02 and OR = 0.45, p = 0.05, respectively). Among patients with acquired MDR TB (n = 14), carriers of the wild genotype of NAT2Arg197Arg(G590G) prevailed (n = 11; 79%), of them 10 were chronic cases and 1 had a relapse. Among patients with DS TB (n = 23), the carriage of the wild genotype of NAT2Arg197Arg G590G was found in 35% of patients (n = 8), of them 7 were new cases and 1 patient suﬀered from chronic tuberculosis.Carriage of a combination of three studied wild genotypes of NAT2Lys268Lys(A803A)×NAT2Arg197Arg(G590G)×NAT2Leu161Leu(C481C) was more often recorded in secondary MDR TB. In secondary MDR TB, the risk of carriage of wild genotypes of NAT2 gene versus primary MDR TB turned out to be high among all cases of diagnosed MDR TB (n = 43, OR = 6.67 [1.28-34.86], p = 0.0277 ) and in the entire sample (n = 65, OR = 11.91 [2.32-61.11], p = 0.0039).Conclusion. The results of genotyping in patients with TB/HIV co-infection and secondary MDR TB are associated with the carriage of acombination of wild genotypes of gene NAT2Lys268Lys(A803A)×NAT2Arg197Arg(G590G)×NAT2Leu161Leu(C481C).